Two smiling women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a portrait of two smiling women. Behind them are people lined up along a portable fence at the National March on Washington for Lesbian and Gay Rights. The Lincoln Memorial appears in the distant background.